مستوى الذكاء المكاني عند طلبة قسم الجغرافية في كلية التربية الاساسية The level of spatial intelligence for geography students in the College of Basic Education - Muhammad Kadhim Mantoob محمد كاظم منتوب (Journal Of Babylon Center For Humanities Studies, 2020)
The paper aims at measuring the spatial intelligence for student of Department of Geography and whether gender affects such skill. The research tackled ( 94 ) student of both sexes . The researcher collected his data via a questionnaire of (44) items . After analyzing data ,one of the most imporaent findings is that student of Department of Geography (College of Basic Education) lack the ability to fully make use of this mental skill. Morever , the gender gap is not a statistic point of view . The researcher stated a few suggestions to polish the students' skills and improve their ability to use spatial intelligence. يهدف البحث الحالي إلى معرفة مستوى امتلاك طلبة قسم الجغرافية في كلية التربية الأساسية للذكاء المكاني ، وهل هناك فروق ذات دلالة احصائية تبعا لمتغير الجنس ؟ تألفت عينة البحث من (94) طالبا وطالبة , صاغ الباحث استبانة مؤلفة من (44) فقرة ، وزعها على طلبة عينة البحث ، بعد التأكد من صدقها وثباتها ، وأهم ما توصل اليه الباحث ، أن طلبة قسم الجغرافية في كلية التربية الاساسية في جامعة بابل لا يتمتعون بدرجة عالية من الذكاء المكاني.كما اشارت النتائج أن لا توجد فروقاً ذات دلالة احصائية تعزى لمتغير الجنس .وفي ضوء ذلك تم اقتراح بعض السبل التي من شأنها ان تنمي قدرات الطلبة في الذكاء المكاني.